Trinuclear [NiFe] Clusters as Structural Models for [NiFe] Hydrogenase Active Sites - Heinemann, Frank Wilhelm; et al. (European Journal of Inorganic Chemistry, 2005)
[Fe(CH3COCH=CHPh)(CO)3] reacts with [Ni(′S 4′)]x (x = 1, 2) or [Ni(′S4C 3Me2′)] [′S4′2- = 1,2-bis(2-mercaptophenylthio)-ethane(2-), ′S4C 3Me2′2- = 1,3-bis(2-mercaptophenylthio)- 2,2-dimethylpropane(2-)] to afford trinuclear [NiFe] clusters [Ni(′S 4′)Fe(CO)32] (1) and [Ni(′S 4C3Me2′)Fe(CO)3 2] (2) and the dinuclear FeIIFe0 complex [Fe(CO)(′S4C3Me2′)Fe(CO) 3] (3). Clusters 1 and 2 have Ni-Fe bond lengths similar to those of active or reduced states of [NiFe] hydrogenases, a sulfur-dominated coordination sphere of Ni and iron-bound CO. Therefore, 1 and 2 may serve as structural model complexes for the [NiFe] hydrogenase active site. Combination of the prime;S4C3Me2′ ligand with FeCl 2·4H2O yielded [Fe(′S4C 3Me2′)]2 (4), the dinuclearity of which suggests that the ′S4C3Me2′ ligand is less flexible than its ethylene-bridged derivative, which affords a tetrameric [Fe(′S4′)]4 complex reported earlier. Compound 4 reacts with 2 equiv. of CO to give [Fe(CO)(′S 4C3Me2′)]2 (5), which like 4 is only sparingly soluble in all common organic solvents. Complex 5 easily loses CO even if stored in the solid state. [Fe(CH3COCH= CHPh)(CO) 3] reacts with 5 to afford 3 as the only product. © Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2005.
UnivIS-Import:2017-03-24:Pub.2005.forsch.sonder.sfb583.trinuc
Keywords: Carbonyl ligands; Cluster compounds; Iron; Nickel; S ligands